Pengaruh Kebijakan Dividen, Keputusan Investasi, dan Profitabilitas Terhadap Nilai Perusahaan: Kasus pada Perusahaan Food And Beverage yang Terdaftar di Index Saham Syariah Indonesia (ISSI) Periode 2021-2022 - Inna Lutfi Yakiya; Wuryaningsih Dwi Lestari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the effect of dividend policy, investment decisions, and profitability on company value (case study of food and beverage companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2021-2022 period). This type of research is quantitative. The data used is secondary data obtained from the company's annual final report. The population in this study is food and beverage companies listed on the ISSI for the 2021-2022 period. There is a population of 47 companies. By using the purposive sampling method during the research period from 2021-2022, a research sample of 26 food and beverage companies listed on the ISSI was obtained with a total of 52 observation data. The data analysis technique uses panel data regression with the Eviews 12 program. The results of this study indicate that dividend policy and investment decisions have a significant effect on company value while profitability does not affect company value.